Determining both sound speed and internal source in thermo- and photo-acoustic tomography. (15th September 2015) - Liu, Hongyu; Uhlmann, Gunther
Abstract: This paper concerns thermoacoustic tomography and photoacoustic tomography, two couple-physics imaging modalities that attempt to combine the high resolution of ultrasound and the high contrast capabilities of electromagnetic waves. We give sufficient conditions to recover both the sound speed of the medium being probed and the source.